EMOTIONAL AND BEHAVIORAL DISORDERS IN PATIENTS WITH EPILEPSY: AN INTERDISCIPLINARY APPROACH - AITETEI KAZBEKOVNA DZHANBOLATOVA , EKATERINA ROMANOVNA GALIMOVA , NAIDA KAZBEKOVNA OSMANOVA , DZHAMILIAT MAGOMEDZAPIROVNA ISAEVA; AISHAT KAMILOVNA ZAYNUDINOVA , ALBINA AKHMEDOVNA HUNAEVA , AMINAT MARATOVNA MAGOMEDRASULOVA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures, which is often accompanied by a wide range of emotional and behavioral disorders. Due to the long-term course of the disease, social stigmatization, side effects of medication, and neurophysiological changes, patients develop persistent psycho-emotional disorders such as anxiety, depression, aggression, and adaptive behavior disorders. Taking into account the complexity of the interaction between neurobiological and psychosocial factors, the study of these disorders requires an interdisciplinary approach that integrates the achievements of neurology, psychiatry, psychology, and social medicine. The purpose of this work is to analyze the emotional and behavioral functioning of patients with epilepsy, as well as to justify the need for a multidisciplinary model for assessing and correcting these disorders. The article presents the results of a clinical, psychological, and psychophysiological study conducted on a sample of adult patients with epilepsy of various etiologies and durations. The obtained data confirm the close relationship between the characteristics of the disease and the severity of behavioral and affective disorders, as well as demonstrate the high importance of psychotherapeutic and social support in the complex of medical measures.